OPERASI DANA SAHAM AMANAH SECARA ISLAM: KAJIAN KES DI PUBLIC MUTUAL BERHAD - Mansor, Fadillah (Jurnal Syariah, 2009)
The objective of this article is to discuss the basic understanding of Islamic unit trust and analyze the performance by evaluating funds that are managed by a particular Fund Manager, that is Public Mutual Berhad. This article explains Shari`a principles, criteria and the Advisory Board roles in the funds operations. It also aims to compare the funds returns performance against the market returns. The KLSI index is used to benchmark the market returns. The main finding of this study is that Islamic unit trust funds outperform the market return in duration of three years, and in years thereafter. Thus, investors stand the opportunity to gain higher returns from investment in unit trust funds by applying proper investment plan. The result is expected to inspire further research pertaining performance of Islamic financial products.